ANALISIS PENERAPAN PSAK NOMOR 45 TENTANG PELAPORAN KEUANGAN ENTITAS NIRLABA (STUDI KASUS PADA MASJID ASSHABIRIN PONTIANAK) - B1031141022, Shahsha Inka (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
Asshabirin Mosque Pontianak is a non-profit entity that is shaped as a place of worship and established in a strategic environment. Based on the explanation, the authors are interested in conducting related research to apply PSAK No. 45 regarding Non-Profit Company Financial Reporting to the financial statements that have been prepared by Masjid Asshabirin Pontianak, to know the financial reporting system applied, to know the constraints in applying PSAK No. 45, and quality information from the reporting itself. The analytical tool used by the authors is the qualitative analysis that is using PSAK No. 45 in preparing financial statements and questionnaires to know the constraints faced by non-profit entities in applying PSAK No. 45. Internal Constraints are (a) the background of the treasurer does not comply with the responsibilities given, and lack of understanding will present the financial statements that are lacking (b) the existence of a mutual agreement among management about financial reporting system. While external obstacles are: (a) there is no socialization and direct education from related parties concerning PSAK No. 45. (b) there is no regulation from the government to make PSAK No. 45 as a reference for the preparation of financial statements.Keywords: Nonprofit Entity, Financial Statement, PSAK 45